FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DI DESA PONTANG KECAMATAN PONTANG KABUPATEN SERANG PROVINSI BANTEN - Himayati, Himayati; Hardiansyah, Muhammad Agus (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Development in the political field is significant in improving the quality of Human Resources. Therefore, the government established a 12-year compulsory education program to create quality human resources. However, participation at the senior secondary level needs to be reminded to reduce the dropout rate. This research was carried out in the Pontang sub-district, Serang district - Banten, using a descriptive qualitative method which is a way and an effort to put more emphasis on aspects of in-depth understanding of a problem. In this method, Creswell (2008) defines the approach is considered as an approach or search to explore and understand a social phenomenon. The data obtained will be analyzed qualitatively and described in descriptive form. To collect, compile, and analyze the results of research.